Analysis of the effect of bilinguals in language learning in different regions of brain using EEG - Krishnamurthy, Priya (2016)
Language training is a process which involves the understanding the various nuances of language such as grammar, semantics, phonetics, vocabulary, pragmatics and syntax. From literature it has been observed that bilinguals demonstrate a higher learning rate in acquiring a new language due to better cognition ability and improved memory. For this purpose, two grammars were presented to subjects who participated in two sessions of training and testing. These were presented by means of different shapes with different colours conforming to the different grammars along with auditory sounds corresponding to the individual shapes presented. The subjects were tested if they were able to recollect the statistical regularities associated with the sense modality, meaning that the subjects would only be able to recognize the sequences pertaining to the grammatical rules presented during the training session. The analysis of the brain response is done by means of acquiring EEG signals during the experiment simultaneously. They were then analyzed by extracting the Event Related Potential after basic pre-processing steps. The ERP waveform consists of two prominent peaks, a negative (N200) and a positive peak (P300), each signifying an event in language perception. A comparative study between the response from grammatical and ungrammatical sequences has been performed showing difference in the response from different areas of the brain. The analysis was quantified using a t-test. It showed that the frontal, central and parietal showed significant difference between the responses obtained from grammatical and ungrammatical sequences compared to the value obtained from the temporal region.